ANTIOXIDANT DEFENSE AND PECULIARITIES OF LIPID PEROXIDATION IN CHILDREN WITH BRONCHIAL ASTHMA - K.I. ISMOILOV; А.М. SABUROVA; М.М. SHARIPOVA (Avicenna Tajik State Medical University, 2017)
Objective: To research peculiarities of the lipid peroxidation and antioxidant system in children with bronchial asthma. Methods: It has taken the results of the research in 56 children aged from 5 to 14 years, who suffered with bronchial asthma (BA). Along with the general clinical examination, spirometry were used to identify respiratory function, and malondialdehyde (MDA) and superoxide dismutase contents in blood serum were analyzed. Results: Spirometry in all BA patients from attack of disease up to attack-free interval showed increasing of forced expiratory volume in 1 second (from 61.5±3.70% to 84.3±5.33%) and maximum voluntary ventilation (from 59.1±4.21% to 81.7±6.31%), and decreasing of residual volume (from 117.4±6.01% to 93.1±5.25%) . Biochemical studies revealed increase in the content of MDA (3.2±0.04), reduced activity of superoxide dismutase (10.7±0.2) and reduced content of ascorbic acid (57.6±0.28) in blood serum in children with BA. Conclusion: At the time of attacks in children lipid peroxidation processes are intensified and followed by increasing development of lipid peroxidation products (MDA), depletion of antioxidant system in blood serum, lower activity of superoxide dismutase, and increased sialic acid, which facilitates development of immune-inflammatory process in the bronchopulmonary system. Administration of Mexidol in children with BA led to earlier elimination of the key clinical and paraclinical implications such as: elimination of asthma attacks, disappearance of pulmonary rale, improved respiratory function parameters, and indicators of lipid peroxidation and antioxidant system in the blood serum.